Sexual and reproductive health literacy and its associated factors among adolescents in Harar town public high schools, Harari, Ethiopia, 2023: a multicenter cross-sectional study - Debella, Adera; Tamire, Aklilu; Bogale, Kasahun; Berhanu, Bekelu; Mohammed, Hanan; Deressa, Alemayehu; Gamachu, Mulugeta; Lami, Magarsa; Abdisa, Lemesa; Getachew, Tamirat; Hailu, Saba; Eyeberu, Addis; et al. (Frontiers in Reproductive Health, 2024)
BackgroundIn sub-Saharan African countries, including Ethiopia, the utilization of sexual and reproductive health information during adolescence is considered to be low. The aim of this study was to assess the level of sexual and reproductive health literacy among adolescents in Ethiopia as well as the factors associated with sexual and reproductive health literacy in this population.MethodsAn institutional-based cross-sectional study design was employed. Systematic sampling methods were used to select 909 study participants. A validated scale was used, consisting of 31 questions with a 5-point Likert scale. A total score was computed, ranging from 31 (minimum score) to 155 (maximum score), which was finally categorized into limited and adequate sexual and reproductive health literacy. A multivariate linear regression model was fitted to determine the factors influencing adolescents’ sexual and reproductive health literacy.ResultsThe percentage of adolescents with slightly adequate and excellent sexual and reproductive health literacy was 38.9% and 6.3%, respectively. On the other hand, 677 (74.5%) participants overall had limited sexual and reproductive literacy. Healthcare workers and reading books were the preferred sources of sexual and reproductive health information that were associated with higher sexual and reproductive health literacy by 6.42 (95% CI 1.62–11.22) and 6.57 (95% CI 1.62–11.22), respectively. Adolescents' ability to pay for their healthcare was associated with better sexual and reproductive health literacy by 13.76 times (95% CI 8.21–19.32).ConclusionMore than three-quarters of the adolescents had limited sexual and reproductive health literacy. Sources of sexual and reproductive health information, including healthcare workers, books, and the Internet, were significantly associated with adolescents’ sexual and reproductive health literacy. Hence, primary stakeholders need to incorporate sexual and reproductive health into the curriculum at high schools.